Extinct Heritage of Leathering History: Historical Leather Factory in Isparta - Ayşe Betül Gökarslan (Art-Sanat)
The Historical Leather (Debbağ-Şayak) Factory was built in the late 19th century on a large land near the Hüseyin Baş Mill, at the intersection of Yenice and Dere Districts of Isparta province. The building, which was used until the 1950s and then changed hands and was used as a thread factory, produced leather, leather, screws and oskar (shoes made of cow leather) for different parts of Anatolia and Istanbul when it was in use as a leather factory. Although the Leather Factory is one of the industrial heritages symbolizing the industrial history of the region, it remained idle, unregistered and not as well-known as the Yalvaç Leather Factory because it could not be used for its original function. In addition to the problems arising from corporate and local governments, serious damage has occurred in the structure, which consists of three different periods, especially as a result of the recent renovations. The building, which has suffered deterioration both from public and user sources, is in danger of collapsing within a few years unless urgent measures are taken. The building is also heavily affected by adverse climatic conditions due to the removal of the upper cover and intermediate floor. This study aims to draw attention to the preservation of an industrial heritage structure belonging to the history of leathermaking, which remains idle but is a very important business branch of Isparta, and solutions on the subject have been developed. Within the scope of this study, on-site observation, documentation with photographs and sketches, and written and visual archive scanning were carried out.